Draft genome sequence of Salmonella enterica subsp. enterica serovar Gallinarum biovar Pullorum strain FCAV198, a Brazilian chicken pathogen - Batista, Diego F.A. [UNESP]; Freitas Neto, Oliveiro C. [UNESP]; Leite, Laura R.; Varani, Alessandro M. [UNESP]; Araujo, Flavio M.G.; Salim, Anna; Almeida, Adriana M. [UNESP]; Ribeiro, Simone A.M.; Oliveira, Guilherme C.; Barrow, Paul A.; Junior, Angelo Berchieri [UNESP] (My University, 2014)
Salmonella enterica subsp. enterica serovar Gallinarum biovar Pullorum is a bird-restricted pathogen which causes pullorum disease. The strain FCAV198 was isolated from a pool of chicken ovaries in Brazil, and its genome may be helpful for studies involving molecular mechanisms related to pathogenesis and other related applications.